2005
DOI: 10.1111/j.1399-0004.2005.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

HJV gene mutations in European patients with juvenile hemochromatosis

Abstract: A large variety of mutations within the genes encoding hepcidin (HAMP) and hemojuvelin (HJV) have been identified in patients with the severe iron overload disorder juvenile hemochromatosis (JH). The aim of the present study was to evaluate the molecular background of JH in patients from central parts of Europe. Sequence analyses of HAMP and HJV were performed in seven JH patients from six families from Germany, Slovakia, and Croatia. For detection of the G320V mutation in HJV, a rapid polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 19 publications
1
33
0
6
Order By: Relevance
“…This finding was supported by subsequent studies by several other groups showing numerous additional mutations of HJV in JH patients (11)(12)(13)(14)(15)(16). In this study, we characterized the processing of HJV expressed in HEK293 cells and identified a binding interaction with neogenin that increases iron accumulation in HEK293 cells.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This finding was supported by subsequent studies by several other groups showing numerous additional mutations of HJV in JH patients (11)(12)(13)(14)(15)(16). In this study, we characterized the processing of HJV expressed in HEK293 cells and identified a binding interaction with neogenin that increases iron accumulation in HEK293 cells.…”
Section: Discussionsupporting
confidence: 71%
“…The proposal that HJV-induced changes in iron homeostasis require interaction with neogenin is supported by the observation that the HJV G320V mutation, the most common mutation in Type 2A HH (6,14), neither interacted with neogenin nor altered intracellular iron levels. Notably, expression of HJV overlapped with that of neogenin in muscles and liver, but not with expression of two other RGM family members, RGMa and RGMb (22)(23)(24)30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no hematologic abnormalities suggestive of the presence of a secondary, anemia-induced iron overload phenotype in mice with liverspecific Alk2 or Alk3 deficiency (supplemental Figure 3). Moreover, hepatic expression of hereditary hemochromatosis diseasecausing genes, including transferrin receptor-2 (Tfr2), 30 Hfe, 31,32 hemojuvelin (Hjv), 9,13,14,33 and ferroportin 1 (Fpn1), 34 did not differ between genotypes (supplemental Figure 4). These results demonstrate a mild iron overload phenotype in Alk2 fl/fl ; Alb-Cre mice and a severe iron overload phenotype in Alk3 fl/fl ; Alb-Cre mice and indicate that both Alk2 and Alk3 have roles in the regulation of systemic iron homeostasis.…”
Section: Liver-specific Deletion Of Alk2 and Alk3 Leads To Iron Overlmentioning
confidence: 99%
“…14 About 30 distinct missense or nonsense point mutations have been identified in the HJV gene leading to JH. 3,15,16 In order to gain insights into the pathogenesis of this disorder and to characterize the functional properties of human HJV, we have studied the biosynthesis and maturation of 5 missense (G99V, 3 C119F, 16 F170S, 17 W191C, 17 and G320V 3 ) and 1 nonsense (R326X 3 ) allelic variants associated with JH. We demonstrate that mutants with defective autoproteolytic processing (F170S, W191C, and G320V) are not correctly targeted to the plasma membrane (PM) but are mainly retained in the endoplasmic reticulum (ER), as observed for the truncated R326X variant.…”
Section: Introductionmentioning
confidence: 99%